2013
DOI: 10.2196/med20.2711
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Technology Competencies for Health Professionals Working in Home Care to Support Older Adults to Age in Place: Outcomes of a Two-Day Collaborative Workshop

Abstract: BackgroundThe demand for care is increasing, whereas in the near future the number of people working in professional care will not match with the demand for care. eHealth technology can help to meet the growing demand for care. Despite the apparent positive effects of eHealth technology, there are still barriers to technology adoption related to the absence of a composite set of knowledge and skills among health care professionals regarding the use of eHealth technology.ObjectiveThe objective of this paper is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 38 publications
2
68
0
1
Order By: Relevance
“…Exposure to home care in nursing schools can influence HCN recruitment if students are better informed about roles and opportunities (Canadian Healthcare Association, ; Home Care Sector Study Corporation, ,; VON Canada, ). Students unprepared for home care do not consider it as a career option and new graduates entering the sector often lack home care experience (Barakat, Woolrych, Sixsmith, Kearns, & Kort, ; Canadian Nurses Association, ; Higuchi et al, ; Home Care Sector Study Corporation, ; Macleod et al, ). Challenges with and high costs of recruitment underscore a need to retain the existing workforce (VON Canada, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to home care in nursing schools can influence HCN recruitment if students are better informed about roles and opportunities (Canadian Healthcare Association, ; Home Care Sector Study Corporation, ,; VON Canada, ). Students unprepared for home care do not consider it as a career option and new graduates entering the sector often lack home care experience (Barakat, Woolrych, Sixsmith, Kearns, & Kort, ; Canadian Nurses Association, ; Higuchi et al, ; Home Care Sector Study Corporation, ; Macleod et al, ). Challenges with and high costs of recruitment underscore a need to retain the existing workforce (VON Canada, ).…”
Section: Resultsmentioning
confidence: 99%
“…Related to the domain inter‐organisational collaboration, shared electronic documentation of patient information was critical to effective collaboration (Doran et al, ). Use of standardised assessment tools, reporting systems, ICT, telehealth and electronic health records in home care can also lead to enhanced monitoring and management of more clients, thereby promoting efficiency (Canadian Healthcare Association, ) and cost savings (Barakat et al, ). ICT used for remote monitoring of clients enabled monitoring of chronic health conditions at a distance, therefore reducing unnecessary hospital, primary care, or home care visits (Barakat et al, ; Canadian Homecare Association, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge and skills necessary to deliver CMM through remote technologies may be acquired and enriched through formal or informal education and training related to telehealth. Telehealth professionals should be able to use remote technologies (hardware and software), recognize and adapt to the drawbacks of remote technologies, establish a communication network with other health care professionals, and apply recognized standards to the use of chosen telehealth technologies …”
Section: Professional Development and Maintenance Of Competencementioning
confidence: 99%
“…A study of community-dwelling individuals with CCDD revealed that they require improved person-centred bi-directional information sharing between patients and their primary care and other care providers (such as specialists and allied health professionals), as well as bi-directional information sharing between different professionals and care providers to improve their care delivery . EMRs and EHRs, telemonitoring and web-based applications and resources may address these needs through improving coordination, continuity and access to services and information for both patients and providers (Barakat 2013;Becker 2014;Burton et al 2004;IHI 2003;Lester 2011;McLean and Sheikh 2009;Pagliari et al 2007;Seto et al 2012).…”
Section: Introductionmentioning
confidence: 99%